2007
DOI: 10.1093/nar/gkm097
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein-mediated maturation of dimer initiation complex of full-length SL1 stemloop of HIV-1: sequence effects and mechanism of RNA refolding

Abstract: Specific binding of HIV-1 viral protein NCp7 to a unique 35-base RNA stem-loop SL1 is critical for formation and packaging of the genomic RNA dimer found within HIV-1 virions. NCp7 binding stimulates refolding of SL1 from a metastable kissing dimer (KD) into thermodynamically stable linear dimer (LD). Using UV melting, gel electrophoresis and heteronuclear NMR, we investigated effects of various site-specific mutations within the full-length SL1 on temperature- or NCp7-induced refolding in vitro. Refolding inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…7). Although the mechanism of the transition between monomers and tight dimers is still a matter of discussion, studies using a 39-mer HIV-1 SL1 or larger leader RNA fragments revealed that this transition could be regulated by the stability of the stem of SL1 during the transition from kissing loops dimers to tight dimers in vitro (Muriaux et al 1996b;Laughrea et al 1999;Shubsda et al 1999;Takahashi et al 2000;Baba et al 2001;Huthoff and Berkhout 2002;Bernacchi et al 2005;Mujeeb et al 2007). Accordingly, the increased stability of extended (À11.3 kcal/mol) versus short (À7.5 kcal/mol) HIV-2 SL1 structures could have a similar negative effect on tight dimerization efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…7). Although the mechanism of the transition between monomers and tight dimers is still a matter of discussion, studies using a 39-mer HIV-1 SL1 or larger leader RNA fragments revealed that this transition could be regulated by the stability of the stem of SL1 during the transition from kissing loops dimers to tight dimers in vitro (Muriaux et al 1996b;Laughrea et al 1999;Shubsda et al 1999;Takahashi et al 2000;Baba et al 2001;Huthoff and Berkhout 2002;Bernacchi et al 2005;Mujeeb et al 2007). Accordingly, the increased stability of extended (À11.3 kcal/mol) versus short (À7.5 kcal/mol) HIV-2 SL1 structures could have a similar negative effect on tight dimerization efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…2) and should migrate similarly on a native TBM gel. However, since the kissing complex conformation depends on the presence of Mg 2+ ions, it should dissociate into monomers while migrating through a TBE gel in which these ions are chelated by EDTA (Mujeeb et al 2007). In contrast, once formed, the duplex conformation will not be affected, as this conformation is not dependent on the presence of Mg 2+ ions.…”
Section: Native Gel Electrophoresis Studiesmentioning
confidence: 99%
“…3B). X55 RNA was snap-cooled and upon the addition of 10 mM MgCl 2 , two sets of samples were prepared: the first set was incubated at 22°C (temperature at which the kissing complex conformation is maintained) for 2.5 h, whereas the second set was incubated for 2.5 h at 55°C (temperature that promotes the conversion of any kissing complex to the duplex conformation) (Mujeeb et al 2007). …”
Section: Native Gel Electrophoresis Studiesmentioning
confidence: 99%
“…The full-length SL1 (SL1-fl, Fig. 1a) is the same 35-nt RNA construct that we have used previously (12, 24, 35). It has the sequence corresponding to the wild-type Lai HIV-1 isolate, except for the inversions in the two terminal base pairs, which enabled optimization of the in vitro transcription yield.…”
Section: Resultsmentioning
confidence: 99%
“…Here the similarities end. It appears that approximately stoichiometric amounts of NCp7 (2 NCp7:2 RNA strands) are required for the full KD-to-ED conversion of SL1wt (12). Assuming the apparent K d of 100 nM (23), about 82% of SL1-fl RNA is bound by NCp7 at the experimental conditions used, and most of the RNA was converted to the ED conformation (12).…”
Section: Discussionmentioning
confidence: 99%